Improving the Profitability, Sustainability and Efficiency of Nutrients Through Site Specific Fertilizer Recommendations in West Africa Agro-Ecosystems Volume 1 (Springer International Publishing, 2018)
Improving fertilizer recommendations for increased return from fertilizer investments and optimized crop response to fertilizer has been a major area of investigation of IFDC. Since 2008, IFDC through its Natural Resource Management (NRM) Program has partnered with national agricultural research services to undertake research, development and extensive on-farm trials in various agroecosystems in West Africa to develop site specific fertilizer recommendations for crops. Validation trials have been conducted in many countries (Benin (maize, cassava), Burkina (rice, maize and sorghum) Ghana (maize, cocoa and cassava) and Togo (maize and cassava). However, these fertilizer recommendation data remain scattered and most of them need final statistical analysis before they can be fully utilized and/or scaled out. As part of its efforts to improve fertilizer use and efficiency in West Africa, and following the recent adoption of the West African fertilizer recommendation action plan (RAP) by ECOWAS, IFDC has taken technical lead with key partner institutions and experts to build on previous and current fertilizer recommendations for various crops and countries in West Africa for wider uptake by public policy makers and fertilizer industry actors.